Medical control dropout in pediatric patients with post-infectious glomerulonephritis history - Troche, Avelina Victoria; Samudio, Margarita (Medicina Clínica y Social, 2024)
Introduction: Post-infectious glomerulonephritis (PIGN) in childhood is a risk factor for the development of long-term chronic kidney disease. Adherence to medical control allows secondary nephroprevention to be carried out. Objective: to evaluate the relationship between risk factors related to non-adherence to medical control of patients with IPGN in a pediatric cohort. Methods: descriptive study, with an analytical component of a retrospective cohort of patients hospitalized between January 2000 and December 2018 in a reference hospital. The relationship between: overcrowding, co-sleeping, maternal and paternal education, number of siblings, cohabitants and origin, with lack of adherence to medical control was analyzed. The chi-square test and logistic regression were used at a significance level of 0.05. Results: a total of 148 patients (103 boys y 45 girls) between 2 and 16 years old (mean age: 8.5± 3.4 years) were included. The lack of adherence was found in 73 patients (49.3%) that was associated with rural origin (p= 0.012, RR: 1.50, 95% CI: 1.10-2.06), low maternal education (p= 0.046, 95%CI: 1.54:1.14-2.08), low paternal education (p= 0.02; RR: 1.483, 95%CI: 1.09-2.01), >3 cohabitants (p=0.007, RR: 1.630, 95% CI: 1.21-2.19), co-sleeping (p=0.026; RR: 1.52, 95% CI: 1.02-2.27) and overcrowding (p
Keywords: sociodemographics factors; glomerulonephritis; chronic kidney disease; pediatrics; nephritic syndrome